Taxonomy of the coastal Thinobius Kiesenwetter (Coleoptera: Staphylinidae: Oxytelinae) in Korea - Lee, Jae-Seok; Yoo, In-Seong; Ahn, Kee-Jeong (Zootaxa, 2021)
A taxonomic study of the intertidal Thinobius Kiesenwetter in Korea is presented. Three species are recognized, two of which are identified as new species (Thinobius jejuensis Lee & Ahn, sp. n. and Thinobius koreanus Lee & Yoo, sp. n.) and Thinobius kuroshio (Sawada) is recorded for the first time in Korea. A key, descriptions, habitus photographs, and line drawings of diagnostic characters of these three species are provided to facilitate identification.